"We might not be citizens but we are still people": Australia's disregard for the human rights of international students during COVID-19. Issue 3 (1st September 2020) - Farbenblum, Bassina; Berg, Laurie
ABSTRACT: Globally, in 2020, the social and economic consequences of lockdown laws during the pandemic disproportionately disadvantaged temporary migrants. In his now infamous statement to visa holders in March 2020, the Australian Prime Minister contrasted "good times" during which "it's lovely to have visitors to Australia" with "times like this" in which non-residents were no longer welcome in Australia. Despite its relative global affluence, Australia excluded temporary visa holders from virtually all government financial support packages. This article empirically examines the impact of these policies on international students in Australia, the largest group of long-term temporary visa holders who, with their limited work rights, have become a de facto low wage migrant workforce in this country. It presents new large-scale data from a July 2020 survey of over 5, 000 international students and recent graduates reflecting widespread inability to pay for essential medical needs, lack of access to secure housing and emergency support, and their experiences of racism, discrimination and social exclusion in Australia during the pandemic. A national and global reckoning with the immediate and long-term impact of government policies on migrants during the pandemic and reinvigoration of the relevance of the human rights framework during "times like this".